The Effect of Topical Breast Milk on Umbilical Cord Detachment in Babies - Sumastri, Heni; Riyanti, Neni (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
Breast milk is an unmatched liquid created by Allah SWT to meet the nutritional needs of the baby and protect it in the fight against possible attacks of disease. The first time it came out was colostrum. Colostrum is high in protein, minerals, vitamin A (Prevents various infections and prevents eye disease), white blood cells (protection against infection) and antibodies (protects against infections and allergies). The main proteins in colostrum are immunoglobulins (Ig G, Ig A, and Ig M), which are used as antibody substances to prevent and neutralize bekteri, viruses, fungi and parasites. The purpose of this study was to find out the topical effect of breast milk on the release of baby umbilical cords in BPM Lismarini and RB Citra in Palembang City. This research method is an experimental research design that has a treatment with the posttest only control group design approach, namely, the baby umbilical cord group that is given topical breast milk after drying in a pack with sterile gauze and baby umbilical cord that is only given sterile gauze or does not give treatment. The study sample was newborns at BPM Lismarini and RB Citra in Palembang City. The sample size in the experimental group was 15 people and the control group was 15. Sample number in BPM Lismarini 30 respondents and RB Citra 30 respondents. It was found that in the topical breastfeeding group of 30 respondent’s as many as 26 people (86.7%) faster (< 5 days) the baby's umbilical cord came off while in the sterile cassation group was obtained only 12 people (40%) out of 30 respondents. Topical influence of breast milk on the release of the baby's umbilical cord in BPM Lismarini and RB Citra in Palembang City, showed that there was an average difference in the length of umbilical cord release in newborns between topical breastfeeding and sterile gauze (p value = 0.000), meaning topical breast milk has a faster effect on cord release in newborns compared to the use of sterile gauze.